Electrochemical detection of As(III) via iodine electrogenerated at platinum, gold, diamond or carbon-based electrodes - Hignett, G; Wadhawan, J; Lawrence, N; Hung, D; Prado, C; Marken, F; Compton, R; Compton, A (2004)
The reaction of iodine, electrogenerated from iodide, is used for the detection of As(III) via electrocatalytic reaction in the diffusion layer of a boron-doped diamond electrode. The merits of this electrode material for this purpose (over platinum, gold or glassy carbon) are demonstrated and the kinetics of the reaction between I2 and As(III) in acid reported.